The INSS Governance System and the Liability of the Managing Servant for Delays in the Granting of Benefits - Smolenaars, Claudine Costa (Journal of Law and Corruption Review, 2022)
The object of this article is the integrity and governance programme instituted by the National Institute of Social Security (INSS) through Ordinances 3.212/19 and 3.213/19. The problem addressed is the scenario of non-compliance of the autarchy with the deadlines for analysis and judicial implementation of benefits provided by Law 8.213/91, leading to the application of fines and official letters reporting crime of prevarication and disobedience of public servants. Will this governance system provide the manager with tools to prove the absence of personal responsibility in decision-making? It is intended to demonstrate that this legal regime of governance can impact the limits of personal liability of public servants. Its specific objectives are to evaluate such Ordinances; to establish a comparison with the decisions of the Federal Regional Courts and the Federal Court of Auditors and, finally, to verify if the autarchy is structured to demonstrate the exemption of responsibility of the manager. The applied methodology includes the deductive method, considering a systemic analysis, with bibliographic review and data collection. The research findings indicate that the INSS integrity and governance programme is still incipient, with a threat of liability falling on the servant, which can be mitigated by data transparency and permanent collaborative governance.